A clavicular overuse injury in a teenage male gymnast: a rare case report - Guedes Almeida, Tiago; De Marco, Giacomo; Vazquez, Oscar; Steiger, Christina; Dayer, Romain; Boudabbous, Sana; Ceroni, Dimitri (Frontiers in Pediatrics, 2026)
Overuse injuries are frequent in young athletes, particularly in gymnasts. However, physeal injuries of the medial clavicle remain exceptionally rare. We report an unusual case highlighting the diagnostic value of magnetic resonance imaging (MRI). A 12.5-year-old male gymnast presented with progressive pain and swelling of the right sternoclavicular joint. Clinical evaluation was complemented by radiographs, MRI, and CT scans to assess the lesion. Imaging revealed irregularity and widening of the medial clavicular physis, associated with synovial capsular dehiscence and enlargement of the articular facet, without signs of infection or inflammation. CT confirmed disturbed endochondral ossification, consistent with a repetitive physeal injury. This case illustrates the susceptibility of growth plates to repetitive stress in paediatric athletes. Medial clavicular physeal injury should be considered in gymnasts with chronic sternoclavicular pain. MRI plays a key role in early and accurate diagnosis.